Safety evaluation of the food enzyme asparaginase from the genetically modified Aspergillus niger strain ASP - EFSA Panel on Food Contact Materials, Enzymes and Processing Aids (CEP); Claude Lambré; José Manuel Barat Baviera; Claudia Bolognesi; Pier Sandro Cocconcelli; Riccardo Crebelli; David Michael Gott; Konrad Grob; Evgenia Lampi; Marcel Mengelers; Alicja Mortensen; Gilles Rivière; et al. (EFSA Journal)
Abstract The food enzyme asparaginase (l‐asparagine amidohydrolase; EC 3.5.1.1) is produced with the genetically modified Aspergillus niger strain ASP by DSM Food Specialties B.V. The genetic modifications do not give rise to safety concerns. The food enzyme was considered free from viable cells of the production organism and its DNA. The food enzyme is intended to be used in the prevention of acrylamide formation in foods and in the processing of yeast and yeast products. Dietary exposure to the food enzyme‐total organic solids (TOS) was estimated to be up to 0.792 mg TOS/kg body weight (bw) per day in European populations. Genotoxicity tests did not indicate a safety concern. The systemic toxicity was assessed by means of a repeated dose 90‐day oral toxicity study in rats. The Panel identified a no observed adverse effect level at the highest dose tested of 1038 mg TOS/kg bw per day, which when compared with the estimated dietary exposure, resulted in a margin of exposure of at least 1311. A search for the similarity of the amino acid sequence of the food enzyme to known allergens was made and no match was found. The Panel considered that the risk of allergic reactions upon dietary exposure cannot be excluded, but the likelihood is low. Based on the data provided, the Panel concluded that this food enzyme does not give rise to safety concerns, under the intended conditions of use.